In vitro susceptibilities of Malaysian clinical isolates of Cryptococcus neoformans var. grubii and Cryptococcus gattii to five antifungal drugs - Tay, S.T.; Tanty Haryanty, T.; Ng, K.P.; Rohani, M.Y.; Hamimah, H. (2006)
The in vitro susceptibilities of Malaysian clinical isolates of Cryptococcus neoformans var. grubii and C . gattii to five antifungal drugs (amphotericin B, flucytosine, fluconazole, itraconazole and ketoconazole) were determined using the Etest method. None of the Malaysian isolates was resistant to amphotericin B and ketoconazole. Isolates resistant to flucytosine, fluconazole and itraconazole were observed in this study. Minimum inhibition concentrations (MICs) of > or = 32 microg ml(-1) against flucytosine, > or = 64 microg ml(-1) against fluconazole and > or = 1 microg ml(-1) against itraconazole were noted in four (8.3), two (4.2) and one (2.1) isolates respectively. There was no significant difference in the MICs for both Cryptococcus species (P > 0.05), indicating that C. gattii was as susceptible as var. grubii to all the antifungal drugs tested. No significant difference in the MICs for both Cryptococcus species collected from 1980 to 1990 and 2002 to 2004 were observed (P > 0.05).